A Critical Appraisal of Laws on Second Trimester Abortion - Marge Berer (e-cadernos ces, 2009)
There will always be women who need abortions after 12 weeks of pregnancy, and their reasons are often compelling. Although second trimester abortions carry relatively more risks than first trimester abortions, abortion is still very safe throughout the second trimester if done in safe conditions. This paper is about law and policy on second trimester abortions, which are allowed on more restrictive grounds than first trimester abortions in most countries, if at all. It focuses on countries where most or at least some second trimester abortions are allowed, including in Europe, where many women are still forced to travel for second trimester abortions, and countries in the developing world, where most second trimester abortions remain unsafe. The need for second trimester abortion should be met in a safe, timely and sympathetic manner. Abortion should be legal at the woman’s request up to 24 weeks and on therapeutic grounds after that, and no other barriers or hurdles should be imposed on women seeking second trimester abortion. In-depth, country-based research is needed, to bring out the facts on second trimester abortion, as evidence of why it should be treated as a legitimate form of women’s health care and supported in public health policy.